Exploring treatment preferences facilitated recruitment to randomized controlled trials. - Mills, N; Donovan, J; Wade, J; Hamdy, F; Neal, D; Lane, J (2011)
OBJECTIVE: To explore how patients' treatment preferences were expressed and justified during recruitment to a randomized controlled trial (RCT) and how they influenced participation and treatment decisions. STUDY DESIGN AND SETTING: Qualitative analysis of audio recordings of recruitment appointments with 93 participants aged 51-70 years in a UK multicenter RCT of localized prostate cancer treatments. RESULTS: Treatment preferences at recruitment were more complex and dynamic than previously assumed. Most participants expressed views about treatments early in appointments, ranging on a continuum from hesitant to well-formed opinions. As recruiters elicited men's views and provided detailed evidence-based treatment and study information, some opted for their preference, but many became uncertain and open to RCT recruitment, often accepting a different treatment from their original "preference." Discussion of treatment preferences did not act as the expected barrier to recruitment but actively enabled many to express their concerns and reach an informed decision that often included RCT participation. CONCLUSION: Exploring treatment preferences and providing evidence-based information can improve levels of informed decision making and facilitate RCT participation. Treatment preferences should be reconceptualized from a barrier to recruitment to an integral part of the information exchange necessary for informed decision making about treatments and RCT participation.